Thermodynamic properties of iron, aluminum, boron and phosphorus in dilute silicon solutions by molecular interaction volume model - Li S.-Y.; Liu K.; Yang F.; Xi F.-S.; Wu J.-J.; Ma W.-H.; Lei Y.; Wang Y.-J.; Zhang X.-N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The thermodynamic properties of impurity components in silicon solutions play an important role in the chemical removal process to the metallurgical route. In this paper, the component activity coefficients and interaction parameters of dilute silicon solutions were estimated by the molecular interaction volume model (MIVM). The activity coefficients (γi) of component i in dilute binary Si-i and ternary Si-i-j solutions at 1687-1873 K were firstly calculated. The concentration dependences of the interaction parameter and activity coefficient were also obtained. The self-interaction parameters (εi,i) for Si-i system were obtained as εB,B= -2.728-362.031/T, εAl,Al = 2.157-1876.776/T, εFe,Fe= -4.842+14445.926/T and εP,P = -2.543+13767.036/T. At the same time, the interaction parameters among components B, Al, and Fe in dilute ternary Sii- j solutions were also derived as εFe,B=-1.2758-2946.306/T, εAl,B = 0.7467-9765.9298/T and εFe,Al= -1.39677+3319.6803/T. Most important of all, the temperature dependences of the interaction parameters and activity coefficients in dilute Si-i and Si-i-j solutions with a certain i or j concentration were deduced. The results show that the predicted self-interaction parameters of B, Al, Fe, and P in binary silicon solutions reasonably agree with the experimental data. This further shows that MIVM is of reliability and can be expanded to a multi-component dilute silicon solution.